VD_FINDINFO HC / 2014 / 551 vom 28. Juli 2014 - VD Tribunal cantonal (2014)
AUTORITÉ PARENTALE, DROIT DE GARDE, ENFANT, CONCLUSIONS, MESURE PROVISIONNELLE, DIVORCE | 133 al. 2 CC, 133 CC, 308 al. 1 let. b CPC (CH), 308 CPC (CH), 317 al. 2 CPC (CH), 317 CPC (CH)